Future Time Perspective and the Achievement of Optimal Best: Reflections, Conceptualizations, and Future Directions for Development - Phan, Huy P.; Ngu, Bing H.; McQueen, Kelvin (Frontiers in Psychology, 2020)
Time is an interesting concept. For some cultural groups, time is an entity that exists only in the here and now, whereas for others it can be linear, emphasizing a person’s past, present, and future. Many of us, while living in the “present moment,” may also anticipate and project future goals, dreams, hopes, and ambitions. Indeed, from a positive point of view, future orientations are healthy and may direct one’s focus, instill motivation and persistence, and mobilize the expenditure of effort. Existing research has provided empirical evidence to support the promotion and encouragement of a positive future time orientation. From an educational point of view, the study of time may be useful for calculating achievement, given that a student may use future time orientation to guide and direct his/her academic and/or non-academic future. One notable question for consideration, in this case, relates to the importance of timespan – that is, how far into the future should one project? There may be a significant difference between, say, a timespan that scopes a 6-month period as opposed to a timespan that scopes a 2-year period. By the same token, over the past few years we have delved into an interesting line of inquiry, namely, the nature of optimal best – for example, what facilitates and/or causes a person to achieve an optimal level of best practice in particular subject matter? Our theory of human optimization, consolidated and recently published in Frontiers in Psychology, provides an in-depth theoretical account of an underlying process, which we postulate could help explain the achievement of optimal best. Optimization, in this case, is intimately linked to a person’s achievement of optimal best. We rationalize that within the context of academic learning, cognitive complexity of particular subject matter could serve as an important source of motivation in the anticipation and projection a student’s extended future timespan. In this analysis, the extremely complex nature of a learning task or a suite of tasks may compel a student to consider a longer future timespan for successful completion. We also argue, in contrast, that the specific duration of a future timespan (for e.g., 6 months vs. 2 years) could play a significant role in the successful optimization of a student’s state of cognitive functioning.